The PD‐1/PD‐L1 axis and human papilloma virus in patients with head and neck cancer after adjuvant chemoradiotherapy: A multicentre study of the German Cancer Consortium Radiation Oncology Group (DKTK‐ROG). Issue 3 (19th May 2017) - Balermpas, Panagiotis; Rödel, Franz; Krause, Mechthild; Linge, Annett; Lohaus, Fabian; Baumann, Michael; Tinhofer, Inge; Budach, Volker; Sak, Ali; Stuschke, Martin; Gkika, Eleni; Grosu, Anca‐Ligia; et al.
Abstract : We examined the prognostic role of PD‐1+ and CD8+ tumor infiltrating lymphocytes (TILs), and PD‐L1+ cells in patients with squamous cell carcinoma of the head and neck (SCCHN) treated with surgery and postoperative chemoradiotherapy (CRT). FFPE samples from 161 patients were immunohistochemically stained for PD‐1, CD8 and PD‐L1. The immune marker expression was correlated with clinicopathologic characteristics, and overall survival (OS), local progression‐free survival (LPFS) and distant metastases free‐survival (DMFS), also in the context of HPV16 DNA/p16 status. The median follow‐up was 48 months (range: 4–100). The 2‐year‐OS was 84.1% for the entire cohort. High PD‐1 and PD‐L1 expression were more common in patients with positive HPV16 DNA ( p < 0.001 and p = 0.008, respectively) and high infiltration by CD8+ TILs ( p < 0.001 for both markers). High PD‐L1 expression correlated with superior OS ( p = 0.025), LPFS ( p = 0.047) and DMFS ( p = 0.048) in multivariable analysis, whereas no significance could be demonstrated for PD‐1. Patients with CD8 high /PD‐L1 high expression had favorable outcome ( p < 0.001 for all endpoints) compared to other groups. We validated the superior OS data on CD8 high /PD‐L1 high using the Cancer Genome Atlas TCGA dataset ( n = 518; p = 0.032). High PD‐L1 expression was a favorable prognostic marker in HPV16‐negative but not HPV16‐positive patients. In conclusion, HPV‐positive tumors showed higher expression of immune markers. PD‐L1 expression constitutes an independent prognostic marker in SCCHN patients post‐adjuvant CRT. In conjunction with CD8 status, these data provide an important insight on the immune contexture of SCCHN and are directly relevant for future treatment stratification with PD‐1/PD‐L1 immune checkpoint inhibitors to complement CRT. Abstract : What's new? Human papillomavirus (HPV)–positivity in squamous cell carcinoma of the head and neck (SCCHN) has been associated with improved response and superior survival rates after radiotherapy and chemoradiotherapy (CRT) compared to patients with HPV‐negative tumors. However, the impact of immune checkpoint contexture in SCCHN treated with adjuvant CRT remains unclear. Here, the authors show that PD‐L1 constitutes an independent prognostic marker. The immune phenotype I (CD8high/PD‐L1high) is more common in HPV16‐positive tumors and associated with favorable patient outcome. The findings provide a rationale for examining the therapeutic potential of using PD‐1/PD‐L1 immune checkpoint inhibitors in combination with CRT in SCCHN.